Effect of graded levels of manganese supplementation on performance and its bio-availability in broiler chicken - SUNDER, G SHYAM; PANDA, A K; GOPINATH, N C S; RAJU, M V L N; RAO, S V RAMA; VIJAYAKUMAR, CH (The Indian Journal of Animal Sciences, 2011)
The effect ofgraded levels ofsupplemental manganese (Mn) on performance and its bioavailability in broiler chickens was studied from 6 to 35 days of age. Day-old commercial broiler chicks (120) were equally distributed into 6 groups with 4 replicates of 5 chicks each, in a completely randomized design and housed in stainless steel three...tier cages. A basal diet based on maize-soybean meal without supplemental Mn was formulated. In addition to the basal diet (Mn 37 ppm) 5 test diets were prepared supplementing Mn at 100,200,400, 800 or 1600 ppm level and fed ad lib. to each test group. Body weight gain, feed/weight gain, giblet and abdominal fat were not influenced by Mn supplementation from oto 800 ppm. However, on increasing Mn supplementation to 1600 ppm, depression in growth, feed conversion ratio and dressing yield was noticed. The retention ofMn in tibia revealed the presence of a linear relationship between Mn intake and its uptake by bone. However, such an increase in Mn deposition did not alter tibia weight or per cent total ash. However, such an increase in Mn deposition did not alter tibia weight or per cent total ash. Similarly, the uptake of Mn by liver, kidney and pancreas tissues increased linearly with the level ofits inclusion in feed. The uptake ofMn was higher in kidney than that in liver or pancreas. Further, the Mn level in diet positively influenced Zn retention in bone. Although, Zn supplementation in diet was kept uniform at 44 ppm, its retention in bone increased significantly with the level of Mn in diet. The study suggested that Mn supplementation up to 800 ppm had no added advantage on broiler performance other than increasing its bioavailability. Supplementation ofMn at 1600 ppm was not desirable.Â